If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3f + -7 = 63 + -2f Reorder the terms: -7 + 3f = 63 + -2f Solving -7 + 3f = 63 + -2f Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Add '2f' to each side of the equation. -7 + 3f + 2f = 63 + -2f + 2f Combine like terms: 3f + 2f = 5f -7 + 5f = 63 + -2f + 2f Combine like terms: -2f + 2f = 0 -7 + 5f = 63 + 0 -7 + 5f = 63 Add '7' to each side of the equation. -7 + 7 + 5f = 63 + 7 Combine like terms: -7 + 7 = 0 0 + 5f = 63 + 7 5f = 63 + 7 Combine like terms: 63 + 7 = 70 5f = 70 Divide each side by '5'. f = 14 Simplifying f = 14
| y=-2.91(0)-30.58 | | y=-2.91x-30.58 | | 3x+4(2x-1)=-2x+6+13x | | C=0.4t+5 | | 4-(8-7)= | | 3x+-4=-3+7 | | 3x-50=x+60 | | 8.1(0)+1.7y=9.3 | | 4(x+7)-5x+2=10 | | 8.1x+1.7(0)=9.3 | | 8.1x+1.7y=9.3 | | 2y^2+7y-49=0 | | 7n+30=-3(8-5n)+16 | | x-4y+6v= | | 3x^2+5x-17+6x+20= | | -4-10-(7-4)= | | 6(r-4)+r+30+-7R= | | -5x+21=-4 | | 49x^2-56x+7=0 | | 2a+7(3-a)=10 | | 154/165=x/100 | | (x-2)*(x^2-2*x-1)=0 | | 36=5t^2 | | 3(2x+7)-5=2(8+4x)-2x | | 5.9x+1.8(0)=6.7 | | 35x^2+22x+3=0 | | 6b+4b-2= | | 5.9(0)+1.8y=6.7 | | 3x^2=17x+28 | | 5.9x+1.8y=6.7 | | 3(x-2)=99 | | 2x+9.75-7x=5.1 |